Highly Integrated Perovskite Solar Cells‐Based Photorechargeable System with Excellent Photoelectric Conversion and Energy Storage Ability - Bi, Jinxin; Li, Shaoyin; Liu, Dongtao; Li, Bowei; Yang, Kai; Xu, Ming; Fu, Chaopeng; Zhao, Yunlong; Zhang, Wei (Energy & environmental materials (Hoboken, N.J.), 2024)
Perovskite solar cells have emerged as a promising technology for renewable energy generation. However, the successful integration of perovskite solar cells with energy storage devices to establish high‐efficiency and long‐term stable photorechargeable systems remains a persistent challenge. Issues such as electrical mismatch and restricted integration levels contribute to elevated internal resistance, leading to suboptimal overall efficiency (ηoverall) within photorechargeable systems. Additionally, the compatibility of perovskite solar cells with electrolytes from energy storage devices poses another significant concern regarding their stability. To address these limitations, we demonstrate a highly integrated photorechargeable system that combines perovskite solar cells with a solid‐state zinc‐ion hybrid capacitor using a streamlined process. Our study employs a novel ultraviolet‐cured ionogel electrolyte to prevent moisture‐induced degradation of the perovskite layer in integrated photorechargeable system, enabling perovskite solar cells to achieve maximum power conversion efficiencies and facilitating the monolithic design of the system with minimal energy loss. By precisely matching voltages between the two modules and leveraging the superior energy storage efficiency, our integrated photorechargeable system achieves a remarkable ηoverall of 10.01% while maintaining excellent cycling stability. This innovative design and the comprehensive investigations of the dynamic photocharging process in monolithic systems, not only offer a reliable and enduring power source but also provide guidelines for future development of self‐power off‐grid electronics. In this work, we developed an integrated photorechargeable system (IPRS) that combines perovskite solar cells with solid‐state zinc‐ion hybrid capacitors. Utilizing a unique ultraviolet‐cured ionogel electrolyte and monolithic design, our devices demonstrate exceptional photorechargeable performance with ultra‐high efficiency and remarkable cycling stability. The IPRS offers increased energy utilization and reduced grid reliance, making it highly promising for off‐grid power and portable electronics applications.